Hoaxes and infodemics: Digital transformation challenges (Case study on Covid-19 pandemic in Indonesia) - Choirul Fajri; Nunung Prajarto; Ana Nadhya Abrar (NOTION: Journal of Linguistics, Literature, and Culture, 2023)
Digital transformation has many implications for society, not only positive, but also negative. Various crimes in the cyber world, including hoaxes and infodemics, are something that cannot be avoided. During the Covid-19 pandemic, the rise of hoax and infodemic news made the handling of Covid-19 in Indonesia more complex. Many people are victims of hoaxes which in the end take action against government policies related to Covid-19, such as reluctance to comply with health protocols and rejection of vaccination programs. This research contributes to studying the challenges of digital transformation in Indonesia, especially during the past Covid-19 pandemic. The research method used in this paper is a case study. Data collection was carried out by in-depth interviews from Ministry of Communication and Information Technology, literature studies, both from books, journals and scientific articles. The results of this study indicate that digital transformation has encouraged the growth of hoaxes and infodemics which have hampered efforts to deal with Covid-19. The Indonesian government needs to take structured actions in dealing with this hoax and infodemic, and make regulations to optimize the digital transformation process.